Estratégias tolerogênicas antígeno-específicas visando profilaxia e terapia na artrite autoimune experimental - Ishikawa, Larissa Lumi Watanabe [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Rheumatoid arthritis (RA) is an autoimmune disease that affects the joints. Most of the therapies used for RA treatment are based on general suppression of immune response, which may increase the susceptibility to infectious agents. The main objective of this work was to establish specific tolerogenic strategies for prophylaxis or therapy of RA. For this purpose, we first established a model of arthritis induced by bovine proteoglycan (PG). Female BALB/c retired breeder mice immunized with bovine PG associated with dimethyl-dioctadecyl ammonium bromide adjuvant developed a typical arthritis characterized by erythema and edema resulting from joint inflammation of one or more paws. Histopathological analysis showed the presence of synovial membrane hyperplasia, inflammatory infiltrates (pannus formation), cartilage destruction and bone erosion. Disease incidence was 100% and the arthritic mice produced significant levels of pro and anti-inflammatory cytokines and IgG1 and IgG2a anti-PG antibodies. Further, we tested the prophylactic potential of PG. Three doses of 50 μg of PG determined a prophylactic effect characterized by a significant decrease in both, arthritis incidence and clinical scores. The decrease in IFN-g and IL-17, as well as the increase in IL-5 and IL-10 production by spleen cells stimulated with PG may be contributing to the prophylactic effect observed in this group. Lastly, we evaluated the therapeutic potential of the combination of active vitamin D (VitD3) with PG. The VitD3+PG association determined a therapeutic effect in experimental arthritis. There was a significant decrease in the clinical scores after VitD3+PG treatment that was confirmed by the histopathological analysis. Most mice paws from the treated group presented well preserved joint structures that were similar to the ones present in healthy animals. Both pro and anti-inflammatory cytokines were decreased after this treatment. No differences were ...

A artrite reumatoide (AR) é uma doença autoimune que compromete as articulações. A maioria das terapias utilizadas para o seu tratamento é baseada na inibição global da resposta imune, podendo aumentar a susceptibilidade a agentes infecciosos. O objetivo geral deste projeto foi definir estratégias tolerogênicas específicas para profilaxia ou terapia da AR. Para isso, em uma primeira etapa, estabelecemos um modelo de artrite induzida por proteoglicano (PG) bovino. Camundongos BALB/c fêmeas retired breeders imunizados com PG bovino associado ao adjuvante brometo de dimetil dioctadecil amônio apresentaram os sinais clínicos característicos da artrite, como eritema e edema decorrentes da inflamação articular de uma ou mais patas. A análise histopatológica mostrou a presença de hiperplasia sinovial, infiltrado inflamatório (formação de pannus), destruição da cartilagem e erosão óssea. A incidência da doença foi de 100% e os animais artríticos produziram níveis significativos de citocinas pró e anti-inflamatórias e anticorpos IgG1 e IgG2a anti-PG. Em uma segunda etapa, testamos o potencial profilático do PG. A inoculação de três doses de 50 μg de PG determinou um efeito profilático caracterizado pela diminuição significativa da incidência da artrite e do escore clínico dos animais. A diminuição da produção de IFN-g e IL-17, bem como o aumento da produção de IL-4 e IL-10 por células esplênicas estimuladas com PG, podem estar contribuindo para o efeito profilático observado neste grupo. Em uma terceira etapa, avaliamos o potencial terapêutico da associação da vitamina D ativa (VitD3) com o PG. A associação VitD3+PG determinou um efeito terapêutico na artrite experimental caracterizado por diminuição significativa do escore clínico. Este feito foi confirmado pela análise histopatológica que revelou que a maioria das patas do grupo tratado apresentou estrutura articular bem preservada, ...
Specific tolerogenic strategies for prophylaxis and therapy in experimental autoimune arthritis
Keywords: Artrite reumatóide; Doenças auto-imunes; Proteoglicanos; Tolerancia imunologica; Vitamina D; Rheumatoid arthritis